Publication of Self-Regulated Learning in Education: A Bibliometric Analysis - Widia Widia; Ida Kaniawati; Lilik Hasanah; Yusi Riksa Yustiana (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2026)
This study aims to analyze international journal articles about self-regulated learning in education published between 2018 and 2022. The research focuses on identifying publication trends, important journals, influential articles, and common research topics related to self-regulated learning. A systematic mapping method was used in four stages. First, relevant articles were collected using the Publish or Perish application connected to the Scopus database. Second, the articles were grouped for bibliometric analysis. Third, the metadata of the articles were checked and completed. Finally, the data were analyzed using the VOSviewer application. The results showed several important findings. First, the number of publications on self-regulated learning changed from year to year during the five-year period. Second, the ten most productive journals published 142 articles related to this topic. Third, the ten most cited articles received a total of 838 citations, showing the strong interest in this research area. Fourth, the most frequently used keywords were “self-regulated learning,” “education,” and “student.” In addition, social sciences had the largest number of publications, followed by computer science, psychology, and engineering. The most common publication types were journal articles, conference papers, book chapters, and review papers. Researchers from many countries and academic disciplines have contributed to studies on self-regulated learning. This study highlights the need for further research, especially in science education, because self-regulation is important for supporting scientific processes, scientific knowledge, and scientific attitudes in learning.